Research study in a manufacturing the determinants of stress in the workplace/ Nur Amira Tanwir and Nur Hananis Johanor - Tanwir, Nur Amira; Johanor, Nur Hananis (2018)
Stress is an adaptive response to a situation that perceived as challenging or threatening to a person’s well-being. The stress response is a complex emotion that produce physiological changes to prepare us for ‘fight or flight’ to defend ourselves from the treat or escape from it. People are stress from workload, information overload, job insecurity and received low salary from employer. Stress also can be seen in a positive side of stress, which is eustress that refers to healthy, positive, constructive outcome of stressful events and the stress response. Employee normally experience stress that affect their job performance and increase their risk of physical and mental health problems (Steven L. McShane, 2008). Stress as a condition or feeling experienced when an individual perceives that demands exceed the personal and social resources the individual is able to mobilize (Lazarus, 2000).